The impact of artificial intelligence and digitalization on journalistic roles - Silva-Rodríguez, Alba; Rodríguez-Vázquez, Ana Isabel; López-García, Xosé (Anàlisi, 2025)
Current technological changes demand a reconfiguration of professional roles in journalism. This research analyses how professional roles in Spanish newsrooms are changing in an environment marked by digitalization and the advance of technologies powered by artificial intelligence. A qualitative methodology is employed, based on semi-structured interviews sent by email to 10 managers from representative media outlets across various sectors (digital press, radio, and digital-native media). This is complemented by an exploratory analysis of job postings for journalists with a technological profile on InfoJobs and LinkedIn over several months in 2025. The objective was to explore how AI is transforming professional roles, skills required, work processes, audience engagement and ethical perceptions regarding its use. The results indicate that although the implementation of AI tools in newsrooms is still limited, there is broad consensus about their potential to optimize repetitive tasks and enhance data analysis. However, there are notable gaps in specific training and in the development of clear ethical guidelines. Most media outlets have not yet incorporated technical roles or new editorial positions related to AI, although the future inclusion of hybrid profiles is viewed positively. The use of AI to facilitate or automate audience interaction is still in its early stages and has not yet been implemented in most cases. Interviewees agree that AI could present an opportunity to strengthen quality journalism if used as a support tool, not as a substitute. In conclusion, the impact of AI on Spanish journalism is in its early stages, with uneven adoption and a lack of systematic strategies for professional, educational and ethical integration in most of the media analysed.